Značaj šumskih zaštitnih pojaseva za regeneraciju zemljišta - Belanović-Simić Snežana; Miljković Predrag; Baumgertel Aleksandar; Beloica Jelena; Ninkov Jordana; Vasin Jovica; Lukić Sara (Glasnik Šumarskog Fakulteta: Univerzitet u Beogradu)
Until now, protective forest belts have mainly been raised around the world with the aim of protecting against aeolian erosion. Nevertheless, they represent multifunctional objects, which, in addition to the primary function of protection against erosion, perform a large number of ecosystem services and represent one of the most frequently applied practices of agroforestry. Protective forest belts are a suitable measure for increasing forest cover, improving soil quality, as well as for the restoration of the agricultural production area in general, thus changing the entire landscape. This paper shows the impact of protective forest belts on carbon storage in the soil. The tree and shrub species in these belts are of particular importance to the state of organic matter in the soil in the belts. The inclusion of these agroforestry measures in the system would significantly contribute to the regeneration of the land area.